White Poplar, Black Locust - Wagenknecht, Louise, 1949- (Book collections on Project MUSE., 2021)
"Growing up in one of the West's last company lumber towns, a small community called Hilt on the California-Oregon border, Louise Wagenknecht witnessed the dying years of a unique way of life. The tail-end of the 1950s lumber boom would devastate the ancient old-growth forests of the Klamath Mountains as well as the people of Hilt, whose lives were inextricably tied to the company lumber mill. White Poplar, Black Locust is the story of that transformation, but it is also something more-a noteworthy addition to the literature of place, and a sensitive and richly textured family memoir. As Wagenknecht unravels the threads that still bind her to both Hilt's history and her own, unforgettable characters emerge, and what should have been the happy ending to this story, the marriage of her divorced mother to a forester working for the Fruit Growers Supply Company, becomes instead the end of childhood innocence, foretelling the demise of the mill and the end of Hilt itself. Originally published by the University of Nebraska Press in 2003, this first book in Louise Wagenknecht's trilogy about life in the Klamath Mountains is now available through Oregon State University Press, together with Light on the Devils (2011) and Shadows on the Klamath (2021)"--